1980
DOI: 10.1111/j.1471-4159.1980.tb09670.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Monoamine Levels in the Cerebral Hemispheres of Microencephlic Rats Treated Prenatally with Methylazoxymethanol or Cytosine Arabinoside

Abstract: Methylazoxymethanol (MAM) injection to rats on day 15 of gestation caused a significant rise in monoamine concentrations (1.6, 2.0, and 2.8 times the control value for serotonin, norepinephrine, and dopamine, respectively) accompanying a decrease in the brain weight and DNA content in the cerebral hemispheres of the offspring at 3 months of age; in the brain stem, these changes were much smaller. Similar change of monoamine concentrations was observed in cytosine arabinoside‐induced microencephaly. The decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Microcephaly could be induced by exposing developing rats to 20 mg/kg MAM when it was injected intraperitoneally to dams on day 13, 14, 15 or 16 of gestation (Spatz and Laquer, 1968). In addition, neuropathological and neurobiochemical studies in the rats have revealed that prenatal MAM exposure also produces neuronal damage in the hippocampal area of the brain (Singh, 1980;Chema and Lauder, 1983) and alterations in the levels of various cerebral neurotransmitters (Johnston and Coyle, 1979;Matsutani et al, 1980). Accompanying these neuroanatomical and biochemical changes, prenatal MAM exposure also results in changes in motor behavior in the offspring examined by photocell systems (Rabe and Haddad, 1972;Cannon-Spoor and Freed, 1984;Kabat et al, 1985), hole-board (Haddad et al, 1981;Vorhees et al, 1984;Plonskey et al, 1985), figure-8 (Vorhees et al, 1984), open field (Ciofalo et al, 1971;Seo et al, 1979;Hanada et al, 1982;Vorhees et al, 1984) and the rotorod (Ciofalo et al, 1971).…”
mentioning
confidence: 99%
“…Microcephaly could be induced by exposing developing rats to 20 mg/kg MAM when it was injected intraperitoneally to dams on day 13, 14, 15 or 16 of gestation (Spatz and Laquer, 1968). In addition, neuropathological and neurobiochemical studies in the rats have revealed that prenatal MAM exposure also produces neuronal damage in the hippocampal area of the brain (Singh, 1980;Chema and Lauder, 1983) and alterations in the levels of various cerebral neurotransmitters (Johnston and Coyle, 1979;Matsutani et al, 1980). Accompanying these neuroanatomical and biochemical changes, prenatal MAM exposure also results in changes in motor behavior in the offspring examined by photocell systems (Rabe and Haddad, 1972;Cannon-Spoor and Freed, 1984;Kabat et al, 1985), hole-board (Haddad et al, 1981;Vorhees et al, 1984;Plonskey et al, 1985), figure-8 (Vorhees et al, 1984), open field (Ciofalo et al, 1971;Seo et al, 1979;Hanada et al, 1982;Vorhees et al, 1984) and the rotorod (Ciofalo et al, 1971).…”
mentioning
confidence: 99%
“…Matsutani et al reported that the activity of tryptophan hydroxylase, serotonine synthesizing enzyme, increased in the cerebrum of a microencephalic rat. 20) They speculated that increase in tryptophan hy-droxylase activity in the microencephalic rat cerebrum resulted in increase of biogenic amines. On the other hand, the physiological function of monoamine oxidase in the synaptic nerve endings is not the inactivation of the aminergic neurotransmitters which are released from presynaptic membrane, although the enzyme can catalyze the oxidative de amination of biologically active monoamines to produce physiologically inactive metabolite products.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical data demonstrated that monoamine levels including 5HT in the cerebral cortex abnormally increased in MAM-rats, whereas the total monoamine content in the cerebral cortex remained unchanged (Matsutani et al, 1980). Thus, the regulatory effect of 5HT axons on target cell differentiation (Lauder and Krebs, 1978) would be altered in the MAM-rats.…”
Section: A Development Of 5ht S O N S In the Cerebral Cortex During mentioning
confidence: 95%
“…In the primary visual cortex of the monkey, the 5HT axons show extremely dense and layer-dependent heterogeneous distribution (Foote and Morrison, 1984;Takeuchi and Sano, 1984). Since elevated monoamine levels have been reported in the cerebral cortex and other brain regions in MAM-rats (Matsutani et al, 1980), some alterations would be recognized in innervation of developing monoaminergic axons, especially 5HT, in the visual system.…”
Section: Role Of Monoaminergic Neurons In Plasticity Of Developingmentioning
confidence: 99%